Pengaruh Iklan dan Citra Merek Terhadap Keputusan Pembelian Produk Madu Wild Bee - Mochamad Yusuf Nuur Fadillah; Iswati Iswati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze advertising and brand image on purchasing decisions for wild bee honey products. This type of research is research with a quantitative approach. The population in this research is all Wild Bee Honey customers. Determining the sample in the study used probability sampling using the Slovin formula so that the number of samples in this study was 97 employees. The data analysis method in this research uses SPSS analysis tools through validity, reliability, classical assumption tests, namely normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t test, F test and correlation and determination coefficients. The results of this research show that (1) Advertising variables influence purchasing decisions, this is proven by the significance value of 0.000 < 0.05. 2. The Brand Image variable has a significant effect on purchasing decisions, this is proven by the significance value of 0.000 < 0.05. 3. Simultaneous test results show that the advertising and brand image variables influence the decision to purchase wild bee honey. This can be proven by the Fcount result of 113.280 or a significance value of 0.000 < 0.05.